Synergistic Cytotoxicity of Newcastle Disease Virus and High-Dose Dimethyl Fumarate in Breast Cancer Cells Is Accompanied by reduction of Selectivity in Normal Cells - Abood, Alyaa Kareem; Salman, Hawraa Dawood; Bedair, Basma H.; Al-Shammari, Ahmed Majeed (Asian Pacific Journal of Cancer Biology, 2026)
Background: Newcastle disease virus (NDV) is a promising oncolytic virus with selective cytotoxicity against cancer cells, while dimethyl fumarate (DMF) is an FDA-approved NF-κB inhibitor showing interesting anticancer activity. The current work assessed the combined cytotoxic effect of NDV and DMF on breast cancer cells and on normal rat embryo fibroblast (REF) cells. Methods: Killing ability was evaluated using crystal violet cytotoxicity assay following treatment with NDV (MOI 1–5), DMF (15.6–500 µg/mL), or their combinations. Drug interaction was measured using the Chou–Talalay combination index. Results: NDV alone showed higher cytotoxicity toward breast cancer cells than toward normal REF cells, confirming its known selectivity. DMF demonstrated dose-dependent cytotoxicity in all tested cell lines. Interestingly, combining NDV with medium–high concentrations of DMF produced strong synergistic effects not only in breast cancer cells but also in normal REF cells. This indicates that DMF eliminates the essential cancer-selectivity of NDV and increases normal-cell susceptibility to the combination treatment. Conclusion: While NDV and DMF display strong synergistic cytotoxicity in vitro, this synergy also induced in normal cells, resulting in a loss of the selective oncolytic nature of NDV. These findings emphasize a major limitation of the combination strategy and highlight the need for dose-optimization studies with lower DMF concentrations or alternative NF-κB inhibitors to preserve selectivity while maintaining anticancer activity.